Case Report: Solid variant of papillary thyroid carcinoma in a young adult with Turner syndrome with chronic thyroiditis - Murakami, Daichi; Hijiya, Masayoshi; Iyo, Takuro; Hayata, Sachiko; Ozaki, Takashi; Enomoto, Keisuke; Kono, Masamitsu; Tamagawa, Shunji; Hotomi, Muneki (Frontiers in Oncology, 2023)
Turner syndrome is associated with an increased risk of developing several neoplasms. In particular, a clinical feature of Turner syndrome with chronic thyroiditis implies a relationship with thyroid malignancies. We report a very rare case of a solid variant of papillary thyroid carcinoma that was identified during a follow-up of chronic thyroiditis in a 22-year-old woman with Turner syndrome. The patient had no notable history of radiation exposure. No genetic mutations relating to the occurrence of the solid variant of papillary thyroid carcinoma, including RET/PTC rearrangements and mutations in the BRAF or RAS, were detected by a gene panel test, namely, the Oncomine™ Dx Target test. To the best of our knowledge, this is the first report of a solid variant of papillary thyroid carcinoma in a young adult with Turner syndrome with chronic thyroiditis. Our case suggests that in patients with Turner syndrome, there may be different pathogeneses from those previously reported, including exposure to radiation or known genetic mutations for the development of a solid variant of papillary thyroid carcinoma.